Molecular characterization of lung cancer: A two‐miRNA prognostic signature based on cancer stem‐like cells related genes. Issue 4 (6th November 2019) - Cheng, Yanping; Yang, Sheng; Shen, Bo; Zhang, Yan; Zhang, Xiaomei; Liu, Tong; Xu, Siyi; Sui, Jing; Yin, Lihong; Pu, Yuepu; Liang, Geyu
Abstract: Lung cancer is one of the deadliest cancers worldwide. To increase the survival rate of lung cancer, it is necessary to explore specific prognosis markers. More and more evidence finds that noncoding RNA is closely associated with the survival of lung cancer, and cancer stem cells (CSCs) also play a significant role in the progress of lung cancer. The objective of this study is to find CSLCs genes that affect the prognosis of lung cancer. The differential expression of long noncoding RNAs (lncRNAs), microRNAs (miRNAs), messenger RNAs (mRNAs) in the Cancer Genome Atlas (TCGA) database and differential expression data from microarray of CD326 + and CD326 − A549 cell are intersected to identify stable and consistent expression genes (2 lncRNAs, 15 miRNAs, and 134 mRNAs). The intersection of lncRNAs and miRNAs is analyzed by univariate and multivariate Cox regression to obtained prognostic genes. Two miRNAs (miR‐30b‐5p and miR‐29c‐3p) are significantly correlated with the overall survival rate. Then using these two miRNAs to construct a risk score model as a prognosis signature of lung cancer. Subsequently, we analyzed the association between two miRNAs and clinical information of lung cancer patients, of which T stage, Neoplasm cancer and risk score ( P  < .05) can be used as independent prognostic indicators of lung cancer. Finally, target genes of 2 miRNAs and 134 mRNAs were annotated with Gene Ontology and analyzed with Kyoto Encyclopedia of Genes and Genomes pathway, and verified with the GEO database. In summary, this study illustrates the role of miRNAs in the promotion of lung cancer by CSCs, which is important to find molecular biomarkers of lung cancer. Abstract : The present study demonstrates the role of microRNAs (miRNAs) in the promotion of lung cancer by cancer stem cells (CSCs), which is important to find molecular biomarkers of lung cancer.